2008
DOI: 10.1016/j.neuroscience.2008.01.079
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemistry of the afferents to the rat cochlear root nucleus: Possible synaptic modulation of the acoustic startle

Abstract: Afferents to the primary startle circuit are essential for the elicitation and modulation of the acoustic startle reflex (ASR). In the rat, cochlear root neurons (CRNs) comprise the first component of the acoustic startle circuit and play a crucial role in mediating the ASR. Nevertheless, the neurochemical pattern of their afferents remains unclear. To determine the distribution of excitatory and inhibitory inputs, we used confocal microscopy to analyze the immunostaining for vesicular glutamate and GABA trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 95 publications
5
17
0
Order By: Relevance
“…As expected from our previous report (Gómez-Nieto et al, 2008b), we found a strong immunoreactivity for VGLUT1 in the cochlear root nucleus (Supplemental Figure 1). VGLUT1-labeled endings equally distributed throughout dorsal and ventral portions of the cochlear root nucleus (Supplemental Figure 1).…”
Section: Resultssupporting
confidence: 92%
“…As expected from our previous report (Gómez-Nieto et al, 2008b), we found a strong immunoreactivity for VGLUT1 in the cochlear root nucleus (Supplemental Figure 1). VGLUT1-labeled endings equally distributed throughout dorsal and ventral portions of the cochlear root nucleus (Supplemental Figure 1).…”
Section: Resultssupporting
confidence: 92%
“…The cochlear root neurons show a latency of 2-3 ms and they respond with a "primary-like with notch" pattern to pure tone stimulation (Sinex et al, 2001). These data suggest that they participate in the acoustic startle reflex Friauf, 1992, 1994;Lee et al, 1996;Gómez-Nieto et al, 2008a, 2008b.…”
Section: Figurementioning
confidence: 86%
“…This is the so-called acoustic nerve nucleus or interstitial nucleus of the vestibulocochlear nerve (mouse: Lorente de Nó, 1926;rat: Harrison and Warr, 1962;Harrison and Feldman, 1970;Merchán et al, 1988;Osen et al, 1991;López et al, 1999). These neurons receive axon collaterals terminating in small boutons arising from the main stem axon of the primary afferents and other noradrenergic and cholinergic afferents from the locus coeruleus and ventral nucleus of the trapezoid body, respectively (López et al, 1999, Gómez-Nieto et al, 2008a, 2008b (Fig. 5).…”
Section: Figurementioning
confidence: 99%
“…Free-floating brainstem sections followed two cycles of freezing and thawing on dry ice, were washed ipn 0.1 M PB and incubated with the corresponding primary antibody (Table 1) as described previously (Gómez-Nieto et al 2008b; Rubio et al, 2008; Gómez-Nieto and Rubio, 2009). Briefly, all immunostaining steps were performed at room temperature (~22°C) unless otherwise stated.…”
Section: Methodsmentioning
confidence: 99%